Working Principles of 3D Xerography - Ling, Pui Foong (2016)
This researchis a continuation of the development of 3D Xerography (3DX).The adhesion force between molten medium density polyethylene (MDPE) particles to a Teflon substratewas investigated. Special attention was placed on the molten state adhesion experiment as it is among the first of its kind to be performed. The experiment was done using the centrifuge method. The particles were placed on substrate, melted and spun at angular velocities up to 17000rpm and analyzed to determine the adhesion force. The experimental results show that the particle adhesion force increases as particle sizesincreases. In other words, the smaller the particle, the higher the tendency it detaches from the substrate. Due to the change in state from solid to liquid, wetting was observed to significantly increase adhesion force. It was further observed that the percentage of particles adhering to the substrate with respect to the adhesion force follows a log-normal distribution which conforms to results from earlier research.